Proposed Marketing Strategy for Enjoy Tour and Travel - Hadianie, Zenie; Aldianto, Leo (The Indonesian Journal of Business Administration, 2014)
Abstract â€“ Nowdays every people need a holiday for entertaining themself after density of their activity. Holiday for every people has been important. Todays how many tour and travel services which is can help us to arrange our holiday so it easier to do a holiday. The business players in the Tour and Travel industry were competing to gain profit by providing various attractive offers so that customer prefer to receipts their services compared to its competitors. Enjoy Tour and Travel participate in providing tour and travel services, especially in Bandung and Jakarta. Enjoy Tour and Travel be operates since 2011. And in 2012 Enjoy Tour and Travel doing the expansion of destination in their business. And nowdays they faced the problem the unsuccessful the expansion and the increasing of the competitor in this industry. The variuous analysis such as external analysis, internal analysis, customer analysis, competitor analysis and SWOT analysis doing to know the root cause of the problem that faced by Enjoy Tour and Travel. The main cause of this problem then grouped by three type, they are the problem of no strategy marketing, the problem of limited financial of company and the problem of barrier to entry is low. To rising this problem, the writer proposed the solution for Enjoy Tour and Travel. The Solution business consist of the proporse the STP and proposed the marketing mix. As for the plan implementation for doing the solution business that proposed consist of plan implementation marketing mix, budgeting financial and plan time activity.Â Keyword : Tour and Travel, Strategy Marketing, Marketing Mix